2021
DOI: 10.1038/s41436-020-01016-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous variants that disturb the transcriptional repressor activity of FOXP4 cause a developmental disorder with speech/language delays and multiple congenital abnormalities

Abstract: Purpose Heterozygous pathogenic variants in various FOXP genes cause specific developmental disorders. The phenotype associated with heterozygous variants in FOXP4 has not been previously described. Methods We assembled a cohort of eight individuals with heterozygous and mostly de novo variants in FOXP4: seven individuals with six different missense variants and one individual with a frameshift variant. We collected clinical data to delineate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Interestingly, the lead GWAS variant in this locus (rs1886814) is less common in Europeans (gnomAD allele frequency = 2.4%) than in East Asians (37.3%), Admixed Americans (18.9%), or South Asians (11.8%) (Karczewski et al, 2020) and was found to be associated with COVID-19 in East Asians by the COVID-19 HGI (COVID-19 Host Genetics Initiative, 2020, 2021. We found that this GWAS signal colocalized with a lung-specific eQTL for FOXP4, a transcription factor associated with neurodevelopmental disorders and congenital abnormalities with lung cancer (Snijders Blok et al, 2021;Yang et al, 2015). Fine mapping with this lung-specific eQTL signal for FOXP4 identified rs1886814 as the variant with the highest likelihood of causality (PPA = 0.870, Figure 4A), which is located $10 kb upstream of FOXP4 and is likely a regulatory variant whose alternative allele is associated with increased FOXP4 expression (effect size b = 0.46; Table S3).…”
Section: Colocalization With Eqtls and Genetic Fine Mapping Of Covid-19 Gwas Signalsmentioning
confidence: 86%
“…Interestingly, the lead GWAS variant in this locus (rs1886814) is less common in Europeans (gnomAD allele frequency = 2.4%) than in East Asians (37.3%), Admixed Americans (18.9%), or South Asians (11.8%) (Karczewski et al, 2020) and was found to be associated with COVID-19 in East Asians by the COVID-19 HGI (COVID-19 Host Genetics Initiative, 2020, 2021. We found that this GWAS signal colocalized with a lung-specific eQTL for FOXP4, a transcription factor associated with neurodevelopmental disorders and congenital abnormalities with lung cancer (Snijders Blok et al, 2021;Yang et al, 2015). Fine mapping with this lung-specific eQTL signal for FOXP4 identified rs1886814 as the variant with the highest likelihood of causality (PPA = 0.870, Figure 4A), which is located $10 kb upstream of FOXP4 and is likely a regulatory variant whose alternative allele is associated with increased FOXP4 expression (effect size b = 0.46; Table S3).…”
Section: Colocalization With Eqtls and Genetic Fine Mapping Of Covid-19 Gwas Signalsmentioning
confidence: 86%
“…Our studies demonstrating that FoxP4 is present in adipose tissues is novel given that FoxP4 has been mainly reported to be expressed in neuronal, pulmonary, gut, and T cells ( 21 , 28 , 35 , 36 ). More specifically, our data provide new evidence that the basal levels of FoxP4 are selectively enhanced in subcutaneous fat tissue, suggesting a potential distinct role of FoxP4 specifically in this depot.…”
Section: Discussionmentioning
confidence: 77%
“…Strong genetic evidence indicates that alterations in the NPFs-ARP2/3 signaling module may lead to ID: copy number variants of the chromosomal region 15q11-q13, encompassing CYFIP1 , were identified in patients with ASD and ID [ 243 ], with several studies indicating a pathogenic role for both increased and decreased CYPFI1 dosage [ 244 , 245 , 246 ]; 21 de novo missense CYPFI2 variants, most of which were shown to impact on WRC-mediated actin remodeling, have been reported in 37 ID patients [ 247 , 248 ]; WASHC4 has been identified as an autosomal recessive ID gene [ 249 , 250 ]; NCKAP1 variants predicted to be deleterious for protein function have been associated with ID [ 251 ]; ABI2 is a candidate autosomal recessive ID gene [ 252 ]; de novo splice site mutations of WASHC5 were shown to cause Ritscher–Schinzel/3C syndrome, a disorder characterized by several phenotypes, among which ID [ 253 ].…”
Section: Cytoskeleton Functions In Neuronal Developmentmentioning
confidence: 99%